‘Seeing Like a Cop’: Police Perception in Spaces of Gender and Racial Criminalization - Russell, Emma K. (The British journal of criminology, 2025)
Building on conceptions of policing as a colonial project, this article contributes to spatial and sensory understandings of policing by examining everyday practices of gender and racial criminalization. I argue that criminalization results from ‘seeing like a cop’ (Guenther 2019), and reordering and securing spaces accordingly. I explore the logics, practices and effects of this regime of visuality and spatial governance, drawing upon research on the criminalization of women who experience interpersonal, state and structural violence in Melbourne, Australia. For these women, police visions of danger, disorder and disposability pre-empt their displacement and punishment. The perceptual practices of police forge carceral continuums that connect the gentrifying streetscape and the home, producing both as sites of racial surveillance and gender entrapment. The article highlights the capacity for sensory analysis to deepen understandings of the violence work of policing.